Use and reuse of amphorae. Wine residues in Dressel 2–4 amphorae from Oplontis Villa B (Torre Annunziata, Italy). (April 2017) - Pecci, A.; Clarke, J.; Thomas, M.; Muslin, J.; van der Graaff, I.; Toniolo, L.; Miriello, D.; Crisci, G.M.; Buonincontri, M.; Di Pasquale, G.
Abstract: Under the aegis of the ongoing international Oplontis Project we carried out organic residue analyses on thirteen samples from eleven Dressel 2–4 amphorae recovered at Villa B at Oplontis (Torre Annunziata, Southern Italy) in order to identify their content and to characterize their visible lining. Although the content of Dressel 2–4 amphorae is usually thought to be wine, no residue analyses have been carried out until now to verify it. Analyses were carried out with Gas chromatography coupled to mass spectrometry. The results of the analyses indicate that all the amphorae were coated with Pinaceae products which had undergone different stages of preparation. Moreover, they confirm that Dressel 2–4 contained wine, or its derivatives, as wine markers were identified in all the samples. The data we obtained demonstrated that the amphorae analyzed were not new vessels, expressly made to trade the wine produced in the surrounding area, but were ready to be reused. Highlights: We analysed 11 Dressel 2–4 amphorae from Oplontis B to identify organic residues. Wine residues were identified in all the amphorae analysed. Pinaceae products were identified in all the samples. Pinaceae products were used as a coating and to seal the stopper. Reuse of amphorae is suggested.